Study of prevalence of overweight and obesity among school going adolescents in north Karnataka and its association with life style changes - Ahammad S., Sameer; A. B., Apurva; Mangshetty, Roopa (International Journal of Contemporary Pediatrics, 2025)
Background: Overweight and obesity in adolescence have become major public health concerns worldwide, including in India, with prevalence rates doubling over the past two decades. Childhood obesity is strongly linked to adult obesity and increases the risk of chronic diseases such as type 2 diabetes, hypertension, cardiovascular disease, and certain cancers. It also negatively impacts bone health, reproductive health, and overall quality of life. This cross-sectional study was conducted to determine the prevalence of overweight and obesity among school-going adolescents and to assess their association with lifestyle factors. Methods: This cross-sectional study was conducted to determine the prevalence of overweight and obesity among school-going adolescents and to assess their association with lifestyle factors. A total of 800 adolescents aged 13–17 years from various private schools in Kalaburagi were included. Data were collected using a semi-structured questionnaire. Anthropometric measurements were taken using standardized methods, and overweight/obesity was classified based on the 2015 Indian academy of paediatrics (IAP) growth chart. Statistical analysis was performed using IBM SPSS version 25.0, with the Chi-square test applied for significance (p<0.05). Results: The study found that 34.3% of participants were either overweight or obese. A significant association was observed between overweight/obesity and various lifestyle factors including diet, screen time, physical activity, and family history. High intake of calorie-dense, processed, and fast food emerged as a major contributor. Conclusions: Despite improvements in health education and recreational opportunities in schools, obesity remains prevalent, highlighting the need for greater awareness and behaviour change at both individual and community levels.